Pengembangan Sistem Pengelolaan dan Pemantauan Proyek dengan Metode Agile Pola Scrum - Adhe Rama Febrianto; Anita Wulansari; Latipah Latipah (Maranatha University Press, 2020)
Vsualproject is a business unit of Visi Prima Group which is located in Gresik, a business engaged in software development. In working on the project, the Vsualproject is required to complete the task on time as well as under the customers' requirement. Current management processes were still done manually which consist of recording in the Whatsapp application chat group. In a software development project, it is also necessary to develop the desired interests to find out whether it is under the organization' demands and needs. Keeping notes in the WhatsApp chat group makes notes frequently disappeared and the search process was more complicated about who requests the development process. The purpose of this research is to develop a system that can help Vsualproject to manage projects and provide services to their customers with the project monitoring feature. The system was developed using the Scrum pattern Agile development method which was carried out during the four-cycle sprints. The results of the development of the system were tested by the Black Box Testing method to ensure that the system meets the user's requirements. The result of this study produced a project management system that can be used by internal users of Vsualproject management projects includes managing the stages, payment, and project’s works. The system can also be used by customers to monitor projects through a web profile without asking for special access rights.